Clinical Characteristics and Treatment Outcomes in Endogenous Cushing’s Syndrome: A 15-Year Experience from Thailand - Wasita Warachit Parksook; Nitchakarn Laichuthai; Sarat Sunthornyothin (Case Reports in Endocrinology)
The most common subtype of endogenous Cushing’s syndrome (CS) is Cushing’s disease (CD), with higher proportions of adrenal CS reported from Asia, compared to other continents. However, little was known about CS in this territory. This study was to investigate the distribution, clinical characteristics, and treatment outcomes of CS in a single tertiary hospital in Thailand. We performed a retrospective evaluation of 82 patients with endogenous CS during 2001–2015. The most common subtype was CD, followed by adrenal CS and ectopic ACTH syndrome (EAS), respectively. Weight gain was the most common presentation. Normal body mass index (BMI), Asian cutoff, was observed in 33% of patients. Specific features of CS (plethora, muscle weakness, bruising, and/or wide purplish striae) were documented in less than half of patients. The median age, adrenocorticotropic hormone (ACTH), and urinary free cortisol (UFC) concentrations were significantly different among 3 subtypes of CS and were highest among patients with EAS. An initial remission rate after transsphenoidal surgeries in CD was 62%, with higher rates in pituitary microadenomas compared to macroadenomas. All patients with unilateral adrenal disease achieved CS remission after adrenal surgeries. Patients with EAS achieved CS remission mostly from bilateral adrenalectomy. The highest mortality rate was observed in the EAS group. These findings were consistent with previous studies in Asia, with more proportions ACTH-independent CS.